Finding the Connectors and Catalysts: A Book Review of The Networked Teacher: How New Teachers Build Social Networks for Professional Support by Kira J. Baker-Doyle - Suzanne L. Porath (Networks: An Online Journal for Teacher Research, 2014)
Kira J. Baker-Doyle opens an important conversation about the support new teachers need to thrive in their first years of teaching with her book The Networked Teacher: How New Teachers Build Social Networks for Professional Support. Few would argue that the first years of teaching are the most stressful, with statistics indicate that about 50% of new teachers leave the profession within the first five years (Smith & Ingersoll, 2004). Some schools and districts provide mentoring programs or new teacher professional development, but Baker-Doyle argues that these traditional programs fail to support new teachers, and especially new teachers of the millennial generation (people who were children between 1990-2000). Traditional support programs tend to re-enforce teacher isolation and the assigned, inflexible curriculum and authoritative policies of the school. Taking a reformed perspective, Baker-Doyle argues that teachers' work is social and their praxis evolves through interaction with their colleagues and when teachers' own questions and professional agency are valued.